(3JMaI GdeNJGQs - (3eLghds
(3ChdgG (B:s
(3bhdg(B: (3ecGaFG deRjOg Cj(B: (3eeGKdG heSGhjG dg hGdeRjO eUOQ ejej ef RGOg Gddg GdfYe, hGdeYfi Cfg jJQLi Cf jchf GdMeO GdPj CJi Hg ehajG HMb GdfYes
(3BNQgG (B:s
(3bhdg(B: (3hjHOd ef GdPjf HUdJg; Cj(B: (3HOd cd ef cd bhdg(B: (3hZjQ GdVGdjf CTGQ Hg Edi Cf dG HeYfi ZjQ bhdg(B: (3ZaGOI Cf GdegJOjf Cj GdePchQjf Hbhdg GdPjJ CfYeJ Ydjges
(3JHUQI GdYfhGf (B:s
(3JdNjU MGTjI GdLed Ydi JaSjQ GdLdGdjfs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJaSjQ hYdhe GdbQBfs